2013
DOI: 10.1007/s11302-013-9366-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the GPR17 receptor, a new target for neurorepair, in neurons and glial cells in patients with traumatic brain injury

Abstract: Unveiling the mechanisms participating in the damage and repair of traumatic brain injury (TBI) is fundamental to develop new therapies. The P2Y-like GPR17 receptor has recently emerged as a sensor of damage and a key actor in lesion remodeling/repair in the rodent brain, but its role in humans is totally unknown. Here, we characterized GPR17 expression in brain specimens from seven intensive care unit TBI patients undergoing neurosurgery for contusion removal and from 28 autoptic TBI cases (and 10 control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…Recent studies highlight the importance of GPR17 in inflammation, neuronal damage sensing, neurorepair, food intake, and myelination (Lecca et al, 2008;Chen et al, 2009;Maekawa et al, 2010;Ren et al, 2012;Franke et al, 2013), but the true identity of the endogenous agonists of the receptor remains controversial. Ciana et al (2006) reported that GPR17 is activated by UDP, UDP-sugars, and cysteinyl leukotrienes, whereas Benned-Jensen and Rosenkilde (2010) reported activation of GPR17 with nucleotides but not with leukotrienes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight the importance of GPR17 in inflammation, neuronal damage sensing, neurorepair, food intake, and myelination (Lecca et al, 2008;Chen et al, 2009;Maekawa et al, 2010;Ren et al, 2012;Franke et al, 2013), but the true identity of the endogenous agonists of the receptor remains controversial. Ciana et al (2006) reported that GPR17 is activated by UDP, UDP-sugars, and cysteinyl leukotrienes, whereas Benned-Jensen and Rosenkilde (2010) reported activation of GPR17 with nucleotides but not with leukotrienes.…”
Section: Discussionmentioning
confidence: 99%
“…Intraneural injection of Ab has been shown to stimulate regeneration of primary sensory axons in the spinal cord (Wu et al, personal communication). The P2Y-like GPR17 has been identified as a sensor of damage of the CNS and participates in lesion repair in the rodent brain and in patients with traumatic brain injury (Franke et al, 2013).…”
Section: Neuroregeneration: Neural Stem/progenitor Cellsmentioning
confidence: 99%
“…In GM, P2Y1, and P2Y12 receptors are involved in astrogliosis in vivo (Franke et al, 2001), and the P2X receptor antagonist PPADS significantly decreases astrogliosis following spinal cord injury in vivo (Rodriquez-Zayas et al, 2012). However, P2X4 and P2Y12 receptors also regulate the microglial injury response (Franke et al, 2013), and the latter are expressed by oligodendrocytes/myelin (Amadio et al, 2006), making it difficult to distinguish specific cellular responses in vivo.Non-Glutamatergic/Purinergic Neurotransmitters in WM As described above, there are a variety of developmental functions now understood for WM glutamatergic/purinergic receptors (Table 1), but functional receptors for GABA-A/B, glycine and to a lesser extent nicotinic, 5-HT, dopamine and adrenoreceptors have also been reported in WM, although their functions remain mysterious (Tables 2 and 3). In a recent study, Fern and colleagues found that mRNA for three quarters of receptor subunits from a panel of non-glutamatergic/purinergic receptors were robustly expressed in WM glial cells, with some found at higher levels than in GM structures (Domingues et al, 2010).…”
mentioning
confidence: 99%